INCIDENCE AND LONG-TERM VISUAL ACUITY OUTCOMES OF RETINAL PIGMENT EPITHELIUM TEARS AFTER INTRAVITREAL ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR TREATMENT OF NEOVASCULAR AGE-RELATED MACULAR DEGENERATION. Issue 4 (April 2019) - Vazquez-Alfageme, Clara; Nicholson, Luke; Hamilton, Robin D.; Patel, Praveen J.
Abstract : Purpose: To report the incidence of retinal pigment epithelium tears in eyes treated with aflibercept for neovascular age-related macular degeneration and compare it with ranibizumab, and to describe long-term visual outcomes of retinal pigment epithelium tears after intensive anti–vascular endothelial growth factor treatment. Methods: Retrospective analysis of clinical charts, spectral domain optical coherence tomography and fundus fluorescein angiography imaging of consecutive naive patients treated with intravitreal aflibercept or ranibizumab for neovascular age-related macular degeneration. Results: Eight hundred consecutive eyes were included in the study (300 treated with ranibizumab and 500 with aflibercept) with 34.0 ± 9.1 months of follow-up. The incidence of tears in the aflibercept group was 3.2% and 2.3% after ranibizumab ( P = 0.52). Twenty-nine eyes with retinal pigment epithelium tears were followed for a mean of 30.76 months. Visual acuity at baseline was 20/100 (50.7 ± 19.3 Early Treatment Diabetic Retinopathy Study letters) and 20/200 (36.1 ± 26.1 Early Treatment Diabetic Retinopathy Study letters) at the end of follow-up. The mean number of injection was 7.3 at 12 months and 13.9 ± 8.1 at the end of the study. The number of injections positively correlated with the final visual outcome. Conclusion: There was a low rate of retinal pigment epithelium tears after aflibercept injections, similar to ranibizumab. The correlation between the number of anti–vascular endothelial growth factors received and visual outcomes supports the need for continuing anti–vascular endothelial growth factor therapy. Abstract : There was a low rate of retinal pigment epithelium tears in patients with neovascular age-related macular degeneration receiving aflibercept which was similar to that of ranibizumab. The correlation between the number of anti–vascular endothelial growth factor injections received and long-term visual acuity outcomes in eyes with retinal pigment epithelium tears, supports the need for continuing anti–vascular endothelial growth factor therapy.